Examining the connection of money laundering and environmental crime: A deep dive into dirty money and trade - Yousop, Nur Liyana Mohamed; Razak, Nazrul Hisyam Ab; Noordin, Bany Ariffin Amin (The Economics and Finance Letters, 2025)
This study explores current research trends on Trade-Based Money Laundering (TBML) within the context of environmental crime through a structured review of academic literature. It then investigates the association between TBML and environmental crime incidents across Southeast Asia. A two-stage methodology is adopted. The first stage systematically reviews studies published between 2006 and 2025, revealing that TBML research remains in its infancy and is principally focused on conceptual frameworks with limited empirical validation. The second stage applies a fixed-effects panel regression, using trade mis invoicing as a proxy for TBML and controlling for corruption, government intervention, and cross-border mobility. The results indicate a positive and statistically significant association between TBML and environmental crime, with the relationship strengthened in jurisdictions marked by higher levels of corruption and weaker enforcement. These findings underline the necessity for coordinated regional action and a holistic policy response to all TBML dimensions. Policymakers should conduct a comprehensive review of Southeast Asian regulatory frameworks to close loopholes, strengthen cross-border cooperation, and deploy real-time fraud detection systems to enhance transparency and deter illicit conduct. Enforcement must remain proportionate to avoid displacing laundering into clandestine channels, striking a balance between vigilant oversight and the facilitation of legitimate trade.